Manejo del estrés en cuidadores de pacientes con demencia, una revisión documental (2021)
The present research has as its central theme the stress management of the caregiver of patients with dementia, taking into account that overload is defined as the result of combinations of physical, emotional and social restrictions, this refers to a psychological state that arises when caring for a sick person. The objective was to identify stress management in caregivers of patients with dementia, through a documentary review. For this bibliographic review, we worked under a qualitative approach, in a documentarytype study, where the information that was acquired came from the consultation of documents, on the other hand, reference was made to the instrument used where the literary review was systematized